A Suzaku sample of unabsorbed narrow-line and broad-line Seyfert 1 galaxies – I. X-ray spectral properties. Issue 4 (14th September 2020) - Waddell, S G H; Gallo, L C
ABSTRACT: A sample of narrow-line Seyfert 1 (NLS1) and broad-line Seyfert 1 (BLS1) galaxies observed with Suzaku is presented. The final sample consists of 22 NLS1s and 47 BLS1s, for a total of 69 active galactic nuclei (AGNs) that are all at low redshift ( z < 0.5) and exhibit low host-galaxy column densities (<10 22 ${\rm cm}^{-2}\, $ ). The average spectrum for each object is fit with a toy model to characterize important parameters, including the photon index, soft excess, Compton hump (or hard excess), narrow iron line strength, luminosity, and X-ray Eddington ratio ( L x / L Edd ). We confirm previous findings that NLS1s have steeper power laws and higher X-ray Eddington ratios, but also find that NLS1 galaxies have stronger soft and hard excesses than their BLS1 counterparts. Studying the correlations between parameters shows that the soft and hard excesses are correlated for NLS1 galaxies, while no such correlation is observed for BLS1s. Performing a principal component analysis (PCA) on the measured X-ray parameters shows that while the X-ray Eddington ratio is the main source of variations within our sample (PC1), variations in the soft and hard excesses form the second principal component (PC2) and it is dominated by the NLS1s. The correlation between the soft and hard excesses in NLS1 galaxies may suggest a common origin for the two components, such as a blurred reflection model. The presented Suzaku sample of Seyfert 1 galaxies is a useful tool for the analysis of the X-ray properties of AGNs, and for the study of the soft and hard excesses observed in AGNs.